EFFECT OF N, Ca, MAP, AND 1-MCP TREATMENTS ON ETHYLENE- IAD INDEX INTERACTIONS DURING APRICOT STORAGE AND SHELF LIFE - Kovač, Renata; Kevrešan, Žarko; Magazin, Nenad; Mastilović, Jasna; Milović, Maja; Kalajdžić, Jelena; Milić, Biserka; Barać, Gordana (Food and Feed Research, 2025)
Aim of this study is to investigate the interrelation between ethylene production, DA index (IAD), and postharvest treatments in four apricot (Prunus armeniaca L.) cultivars: ‘Buda,’ ‘NS Kasnocvetna,’ ‘NS Rodna,’ and ‘NS6.’ Apricots were harvested with IAD values between 0.41–0.80, stored at 1°C for 15 days, followed by 3 days of shelf life at room temperature. Ethylene production and IAD were measured at harvest, after cold storage, and after shelf life. Preharvest treatments included nitrogen (N) and calcium (Ca), while postharvest treatments included modified atmosphere packaging (MAP) and 1-methylcyclopropene (MCP). Results showed cultivar-specific ethylene responses and IAD, with 'Buda' exhibited the most rapid decline of IAD and highest ethylene levels, and 'NS6' showing a lower decrease of IAD, especially under MAP and Ca treatments. Postharvest treatments effectively reduced a decrease of IAD for all tested cultivars. The findings highlight the need for cultivar-specific calibration of the IAD index to optimize the management of apricots at a given ripeness stage, thereby maintaining their overall quality and storage capability.
Keywords: stone fruit; postharvest; DA meter; preharvest treatments